Could excision repair cross‐complementing group‐1 mRNA expression from peripheral blood lymphocytes predict locoregional failure with cisplatin chemoradiation for locally advanced laryngeal cancer?. Issue 2 (15th October 2019) - Raturi, Vijay Parshuram; Wu, Chen‐Ta; Mohammad, Suhel; Hojo, Hidehiro; Bei, Yanping; Nakamura, Masaki; Okumura, Masayuki; Rachi, Toshiya; Singh, Rahul; Gupta, Rajeev; Parmar, Devendra; Hasan, Feza; et al.
Abstract: Aim: The association of excision repair cross‐complementing 1 mRNA (ERCC‐1 mRNA) expression with the outcome has been reported with immunohistochemistry (IHC) using tumor tissue in head and neck cancer. We evaluated ERCC‐1 mRNA expression by reverse transcription polymerase chain reaction (RT‐PCR) from peripheral blood lymphocytes (PBLs) as bio‐predictor of locoregional failure (LRF) to chemoradiation (CRT) for locally advanced laryngeal squamous cell cancer (LALSCC). Methods: A total of 107 male patients with LALSCC were enrolled in this prospective study. ERCC‐1 mRNA expression by PBLs was determined by RT‐PCR. Definitive CRT was delivered with 35 mg/m 2 weekly cisplatin. Response Evaluation Criteria in Solid Tumor 1.1 (RECIST 1.1) were used in evaluating treatment response. The primary objective was to assess LRF. The influence of patient characteristics, treatment response, weekly cisplatin cycles, ERCC mRNA expression was determined for LRF, progression‐free survival (PFS) and overall survival (OS). Results: A total of 98 patients completed definitive CRT. The median value of 2‐ΔΔCT ERCC‐1 mRNA expression was 3.9; based on which it was categorized as low and high. Correlation of ERCC‐1 expression with treatment response was insignificant (P‐ .38). With a median follow‐up of 33 months; 2‐year LRF, PFS, and OS was 63.3%, 34.7% and 79.4%. The 2‐year LRF, PFS and OS for low versus high expression were 53.1% versus 73.5% ( P ‐value = 0.036), 44.9% versus 24.4% ( P ‐value = 0.047) and 81.6% versus 77.2% ( P ‐value = 0.33), respectively. In multivariate analysis, ERCC‐1 expression, T‐stage, N‐stage and tumor subsite are predictive factors for LRF; T‐stage and nodal recurrence for OS; stage and treatment response for PFS. Conclusion: LALSCC patient with ERCC‐1 mRNA low expression was associated with lower LRF rate, and improved PFS.